The efficacy and safety of negative pressure wound therapy in paediatric burns: a systematic review and meta-analysis of randomized controlled trials - Jiaqi Lou; Xiaoyu Zhu; Ziyi Xiang; Youfen Fan; Jingyao Song; Neng Huang; Jiliang Li; Guoying Jin; Shengyong Cui (BMC Pediatrics)
Abstract Background Although the effective application of negative pressure wound therapy (NPWT) has been exemplified in diverse clinical studies, its potential and safety, specifically regarding paediatric burns, are yet to be fully confirmed. Our most recent systematic review and meta-analysis strive to investigate the impact of NPWT within the realm of paediatric burns. Methods We sourced relevant articles from databases including PubMed, Embase, the Cochrane Database, Web of Science, the International Clinical Trials Registry Platform, China National Knowledge Infrastructureris, the VIP Database for Chinese Technical Periodicals, and the Wanfang database. We defined the primary outcome measure as the healing time, while healing rate, numbers of dressing changes, detection rate of positive bacteria, incidence rate of adverse reactions, scar scale scores, and treatment costs were considered as secondary outcome measures. Pooling of data was conducted and the results were articulated as relative risk (RR), mean difference (MD), and standardized mean difference (SMD), all with a 95% confidence interval (CI). Results In this systematic review and meta-analysis, a total of 12 studies involving 1033 individuals were examined, including 559 paediatric burn patients who underwent NPWT (referred to as the treatment group) and 543 patients who received treatments other than NPWT (referred to as the control group). The amalgamated data from these studies exhibited that the treatment group experienced significant reductions in healing time (SMD = -1.60; 95% CI: -2.26 - -0.95; p < 0.001, I2 = 92.8%), the number of required dressing changes (SMD = -4.6; 95% CI: -5.84 - -3.36; p < 0.001, I2 = 92.4%), positive bacteria detection rate (RR = 0.61; 95% CI: 0.26–1.46; p = 0.004, I2 = 81.8%), incidence of adverse reactions (RR = 0.61; 95% CI: 0.33–1.12; p = 0.005, I2 = 68%), scar scale scores (SMD = -1.66; 95% CI: -2.54 - -0.79; p < 0.001, I2 = 89.4%), as well as in treatment costs (SMD = 0.92; 95% CI: -1.66–3.49; p < 0.001, I2 = 98.4%). Additionally, these individuals showed an increased rate of healing (RR = 1.17; 95% CI: 0.99–1.39; p < 0.001, I2 = 78%). Subgroup analysis did not find that the degree of burn was one of the sources of high heterogeneity. Conclusion Our meta-analysis points to the effectiveness of NPWT in treating paediatric burns. Notably, it significantly mitigates healing duration, frequency of dressing alterations, positive bacterial detection rate, adverse reactions incidence, scar scale scores and treatment costs, all while propelling the acceleration of wound healing.